Removal of kraft lignin from aqueous waste solution using emulsion liquid membrane - Choo, Ching Li, 1989-, author; Norasikin Othman, supervisor; Fakulti Kejuruteraan Kimia (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2013)
Project Paper (Sarjana Muda Kejuruteran (Kimia)) - UniversitiTeknologi Malaysia, 2013